Correlation analysis of satisfaction with subspecialty management model in operating rooms: a cross-sectional survey in China - W. Wang; J. Shen; Y. Ma; Y. Chen; R. Gong; Q. Qian; Y. Sun (BMC Nursing)
Abstract Background The operating room (OR) presents a highly demanding environment due to its complexity in clinical work. This study examines the sub-specialty management model of operating rooms from various evaluative perspectives. We intend to assess the influence of this model on overall operating room quality using a scientific methodology, thereby establishing a foundation for future optimization of operating room management. Materials and methods In September 2024, a convenience sampling method was employed across 22 provinces, five autonomous regions, and four municipalities directly administered by the central government. A total of 731 hospital surveys were disseminated. The questionnaire encompassed five dimensions: specialty care, nursing care quality, academic research, patient satisfaction, and nursing growth Through reliability analysis, validity analysis, correlation analysis, and regression analysis, we investigated the relationships among these variables and their influence on satisfaction with the OR subspecialty management model. Result Descriptive statistical analysis indicated that “specialty care” attained the highest overall evaluation, with a mean score of 4.51 ± 0.420. Examination of Dimensional Variations among Hospitals of Distinct Grades.Significant differences exist in speciality nursing (t = 2.890, p < 0.001) and nurse growth (t = 1.997, p < 0.05) between tertiary and secondary medical institutions, with tertiary institutions exhibiting superior performance in speciality nursing mean (4.528 ± 0.404) and nurse growth mean (4.120 ± 0.415). Correlation analysis revealed a significant positive correlation (p < 0.001) among speciality nursing, nursing quality, scientific research and academia, nurse-patient satisfaction, and nurse growth. Conclusion The sub-specialty management model for operating rooms has markedly enhanced the professionalism and safety of surgical procedures, emerging as a pivotal trend in contemporary operating room management. The creation of a specialized management evaluation model for operating rooms offers a robust scientific foundation for enhancing operating room management. The enhancement of operating room management efficiency can be significantly achieved by fortifying specialty nursing, advancing nurse career development, and elevating scientific research and service quality through multidimensional collaborative improvements, thereby promoting the quality and advancement of subspecialty management in operating rooms.